Phase III trial comparing the efficacy and safety of recombinant‐ or urine‐derived human chorionic gonadotropin for ovulation triggering in Japanese women diagnosed with anovulation or oligo‐ovulation and undergoing ovulation induction with follitropin‐alfa. (4th December 2016) - Ikenaga, Hideyuki; Tanaka, Yudai; Shiotani, Masahide; Rogoff, Daniela; Shimizu, Shin; Ishihara, Osamu
Abstract: Aim: Outside of Japan, recombinant‐human chorionic gonadotropin (r‐hCG) is widely used for the induction of final follicular maturation and early luteinization in women undergoing ovulation induction; whereas in Japan, urine‐derived hCG (u‐hCG) is predominantly used. The primary objective of this study was to demonstrate the non‐inferiority of r‐hCG to u‐hCG for ovulation induction, as assessed by the ovulation rate. Methods: This was an open‐label, parallel‐group, randomized, multicenter, phase III trial in Japanese women with anovulation or oligo‐ovulation secondary to hypothalamic–pituitary dysfunction or polycystic ovary syndrome, undergoing ovulation induction with recombinant‐human follicle‐stimulating hormone. The women were randomized (2:1) to receive either a single 250 μg s.c. dose of r‐hCG or a single 5000 IU i.m. dose of u‐hCG for ovulation triggering. Results: Eighty‐one women were randomized to either r‐hCG (n=54) or u‐hCG (n=27). Ovulation occurred in 100% of the participants and treatment with r‐hCG was observed to be non‐inferior to u‐hCG for ovulation induction. Overall, the type and severity of adverse events were as expected for women receiving fertility treatment. Conclusion: This study demonstrated that r‐hCG was non‐inferior to u‐hCG for inducing ovulation. Furthermore, r‐hCG demonstrated an expected safety profile, with no new safety concerns identified.